Regulasi Hukum Siber dan Pembatasan Kebebasan Berekspresi: Studi Perbandingan antara Indonesia dan Singapura - Addinda Khairunnazah; Ahmad Fikri Hilal; Alfath Fadila Mursyid; Fatimatu Zahra; Ade Fartini (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The rapid development of information and communication technology has driven the transformation of human activities into the digital realm, making cyber law regulation an essential need to govern activities in the virtual world. This research discusses the comparison of cyber law regulations in Indonesia and Singapore, specifically the Electronic Information and Transactions Law (UU ITE) and the Cybersecurity Act as well as the Protection from Online Falsehoods and Manipulation Act (POFMA), focusing on legal philosophy, enforcement mechanisms, and the protection of freedom of expression. A normative legal research method with a comparative approach is used to analyze the normative context, law enforcement implementation, and the social impacts of both regulations. The research findings indicate that Indonesia adopts a repressive legal approach with fragmented enforcement and challenges related to digital literacy, which leads to potential restrictions on freedom of expression. In contrast, Singapore applies a risk-based regulatory framework with centralized coordination and a more adaptive mitigation approach, aiming to balance content control with the protection of human rights. This research recommends reforms and strengthening of cyber law regulations in Indonesia to improve law enforcement effectiveness and ensure proportional freedom of expression in the digital era.